Biliary slage as a stage of gallstone disease: the successes and difficulties of treatment - O. N. Minushkin; T. B. Topchiy; E. G. Burdina; E. V. Novozhenova; Yu. E. Tugova (Медицинский совет, 2021)
Introduction. The high prevalence rates of biliary sludge and its frequent development into the stone stage of cholelithiasis constitute grounds for studying this issue, as the effective action on biliary sludge can prevent overall disease progression.Purpose of the study. To determine the options for diagnosis of biliary sludge in the polyclinic settings. Objectives: 1) Estimate the frequency of diagnosis of biliary sludge. 2) Assess the features and dependence of treatment on the type of biliary sludge. 3) Assess the outcome of treatment depending on the follow-up managing of patients. 4) Propose an algorithm for managing patients after biliary sludge has been diagnosed.Materials and methods. In the work used data of the clinics of the President of the Russian Federation. The total number of people surveyed for 1 year was 1.117. These patients underwent an ultrasound examination (dispensation) and 218 were fitted with biliary sludge (BS), which was 19.4%. Of the 70 patients with BS, 4 groups were formed: 1st group (20 patients) with BS type, 2nd (20 patients) – with BS type, 3rd (20 patients) – with BS type, 4th (10 patients) – with BS-type (BSS) type.All patients received Exchhol therapy at the rate of 15 mg/kg of weight; patients with a pronounced spastic component in the sphincter system – myotropic spasmolytic Sparex (20 mg x 2 times a day); patients of the 4th group (with a near-located sediment indicating the presence of inflammation) – Adisord (derived nitrofuran) 200 mg x 4 times a day (5 days).Results. The type of precipitation was cupped in 4 weeks of treatment; Type – for 8–12 weeks of treatment, type V – for 13–14 weeks.Conclusions. The presented data allow us to hope that early diagnosis of biliary sludge and the factors of its development will help start timely treatment and prevention of the disease.